2020
DOI: 10.1055/s-0040-1709528
|View full text |Cite
|
Sign up to set email alerts
|

Closed Incisional Negative Pressure Wound Therapy at Flap Suture Line: An Innovative Approach for Improving Outcomes in Suboptimal Wound Conditions

Abstract: Background Persistent dead space following flap cover is a frequently encountered challenge following the reconstruction of complex wounds. It may lead to a hematoma, seroma, wound infection, and wound dehiscence. Wound dehiscence could be a devastating complication. Closed incisional negative pressure wound therapy (ciNPWT) over the surgical incisions was found to reduce surgical site infection (SSI) and wound dehiscence. We applied this principle at the closed flap suture line and through this article, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The midway point of this zone at StO 2 values of 72.5% has a sensitivity of 86% and specificity of 86% for predicting SFN. This would suggest that for skin flaps with StO 2 measurements below 72.5% and above 60%, perfusion has been compromised but may still be salvageable with adjuncts such as hyperbaric oxygen, 15 topical vasodilators, 16,17 negative pressure dressings, 18 and avoidance of additional insults such as compressive dressings, smoking, pressure, hypoxia, and hypotension. 19,20 This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The midway point of this zone at StO 2 values of 72.5% has a sensitivity of 86% and specificity of 86% for predicting SFN. This would suggest that for skin flaps with StO 2 measurements below 72.5% and above 60%, perfusion has been compromised but may still be salvageable with adjuncts such as hyperbaric oxygen, 15 topical vasodilators, 16,17 negative pressure dressings, 18 and avoidance of additional insults such as compressive dressings, smoking, pressure, hypoxia, and hypotension. 19,20 This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although some recent published articles report that prophylactic use of NPWT following surgery may be associated with fewer SSI, there is controversy surrounding this topic. [8][9][10][11][12][13] Using a nationwide database, this study aims to investigate the outcome of prophylactic negative pressure wound treatment (NPWT) in colorectal cancer operations. We speculated that a prophylactic NPWT would be associated with less postoperative wound infection following colorectal cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The first indications for these devices included open fractures and chronic, high-risk, lower extremity wounds [9,2]. As techniques and technology have advanced, NPWT has become a safe and established method for improving surgical site related outcomes in select patients [1,14,15]. The cost effectiveness of NPWT remains controversial, though many studies have found it to be cost-neutral, if not cost saving, in a majority of applications [12,16,28].…”
Section: Introductionmentioning
confidence: 99%